A simulation chain for reflectometry and non-linear MHD: type-I ELM case. (20th December 2021) - Vicente, J.; da Silva, F.; Hoelzl, M.; Conway, G.D.; Heuraux, S.
Abstract: A complete chain from a non-linear MHD plasma model simulation through full-wave code simulations implementing synthetic conventional reflectometry is established. For this purpose, the two-dimensional full-wave code REFMUL is employed together with MHD descriptions obtained from the JOREK code. First results of the integrated modeling are presented here where a type-I ELM crash, leading to a fast collapse of the H-mode pedestal, was taken as case-study. The REFMUL simulations were customized to implement synthetic reflectometry in conventional set-up using fixed frequency probing with O-mode waves. Posing challenging conditions for reflectometry, the type-I ELM crash reveals some of the merits and caveats of the diagnostic technique. This work also opens up the possibility to extend modeling to other MHD or ELM studies and provide support to experimental observations with reflectometry.